UPAYA HUKUM DAN PENYELESAIAN WANPRESTASI SERTA OVERMACHT DALAM PERJANJIAN LEASING - Rudi Prasetiya (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT The contents of the operating lease agreement with regard to the announcement of the Directorate General of Monetary No. PENG-307 / DJM / III.1 / 7/1974 concerning Guidelines for the Implementation of Leasing Regulations are: Provisions regarding the object of the agreement; Duration of the agreement; Rental price; Method and place of payment; Rights and obligations of the parties; Delivery (delivery date and delivery limit); End of agreementConstraints faced in lease contracts include, among others, the regulations regarding leasing provisions in Indonesia are still underestimated, that Indonesia still has not specifically regulated the law concerning leasing, technical constraints are that the lessor requires experts who are in their respective fields and who have special control. issues related to the lease agreement. After the lessor experiences the above problems, the lessee itself usually faces obstacles in the form of pressure that large funds must be provided to supply capital goods to the lessor. So like it or not, the lessee has agreed to the agreement they made and the terms that have been included by the lessor even though the lessee is reluctant to agree to these terms because in this case, the lessor is fully responsible for all risks and constraints in the lease agreement.Legal remedies and settlement of defaults and overmatches include: In the event of default in the form of late payment of rent, the lessor has the right to pay a penalty for the late payment of the amount specified in the agreement However, in practice, the lessor will give a warning either verbally (by telephone) or by letter to the lessee. The lessor also still provides a grace period for the lessee to settle the arrears of rent to the lessor and in the event of a late payment made less than three days from the due date, the lessee is not subject to penalty; In the case of default in the form of pawning of capital goods and transfer of the right to lease capital goods to a third party, the lessor immediately takes the following actions: a day after it is discovered that the collateral is being pawned, the lessor immediately sends its informant team to withdraw the capital goods based on the power of attorney issued. made by the parties at the same time as the signing of the lease agreement between brands; In the case of the lessee who is accused of negligence and is asked to give him a sanction for his negligence, he can defend himself by submitting a reason to free himself from the sanction. The reason for the lessee to free itself from sanctions for negligence, one of which is by filing a demand for an overmatch. Keywords: Default, Leasing